High-fidelity ATP imaging via an isothermal cascade catalytic amplifier. Issue 41 (11th October 2022) - Zou, Zhiqiao; Pan, Min; Mo, Fengye; Jiang, Qunying; Feng, Ailing; Zhou, Yizhuo; Wang, Fuan; Liu, Xiaoqing
Abstract : An on-site activated aptasensing platform is constructed for highly reliable ATP monitoring in cancer cells both in vitro and in vivo by combining tumor-specific activatable MnO2 with the stimuli-responsive cascade DNA amplifier. Abstract : Artificial catalytic DNA circuits that can identify, transduce and amplify the biomolecule of interest have supplemented a powerful toolkit for visualizing various biomolecules in cancer cells. However, the non-specific response in normal tissues and the low abundance of analytes hamper their extensive biosensing and biomedicine applications. Herein, by combining tumor-responsive MnO2 nanoparticles with a specific stimuli-activated cascade DNA amplifier, we propose a multiply guaranteed and amplified ATP-sensing platform via the successive cancer-selective probe exposure and stimulation procedures. Initially, the GSH-degradable MnO2 nanocarrier, acting as a tumor-activating module, ensures the accurate delivery of the cascade DNA amplifier into GSH-rich cancer cells and simultaneously provides adequate Mn 2+ cofactors for facilitating the DNAzyme biocatalysis. Then, the released cascade amplifier, acting as an ATP-monitoring module, fulfills the precise and sensitive analysis of low-abundance ATP in cancer cells where the catalyzed hairpin assembly (CHA) is integrated with the DNAzyme biocatalyst for higher signal gain. Additionally, the cascade catalytic amplifier achieved tumor-specific activated photodynamic therapy (PDT) after integrating an activatable photosensitizer into the system. This homogeneous cascade catalytic aptasensing circuit can detect low-abundance endogenous ATP of cancer cells, due to its intrinsically rich recognition repertoire and avalanche-mimicking hierarchical acceleration, thus demonstrating broad prospects for analyzing clinically important biomolecules and the associated physiological processes.